ACADEMIC AND NON-ACADEMIC LANGUAGE SOCIALIZATION FOR INTERNATIONAL STUDENTS AT AN INDONESIAN PUBLIC UNIVERSITY - Suryadi, Adi Irma (International Journal of Education, 2023)
Academic language socialization refers to the process of helping students to gain knowledge of the language and an ability to participate in new discourse communities by using the language appropriately. Previous research mostly discussed language socialization from students’ perspectives in overseas, such as in Taiwan, America, and Malaysia. In Indonesia, academic language socialization is still less explored, whereas Indonesia is incessantly to internationalize the university by receiving international students from around the world. Therefore, this research is designed to explore academic language socialization for international students from the university administrators’ perspectives, focusing on the university policies, academic and non-academic supports, and challenges. To collect the data, the researcher interviewed five participants; the director of postgraduate, the head of department of masters in Economics and Development Studies, the head of the language centre, one lecturer, and one international student. In addition, the researcher also did classroom observations, [W1] and document analysis (i.e., policy documents). By using interactive data analysis by Miles, et al. (2014), the findings revealed that there were gaps between the applicable policies and implementations.[W2]  To overcome the gaps, the university provided academic and non-academic support. For academic supports, the university provided the language center support for international students to have Indonesian language training both for general purposes, and academic purposes. For non-academic supports, the university provided the international students with some facilities, such as housing, cultural studies, vacation together, and art and culture festival. However, there were also several challenges both from bottom-up and top-down perspectives. The challenges were the results of the gaps between the applicable policies and implementations in receiving international students at the university. This result implies the need to reformulate policies of recruitment of international students and provide better academic and non-academic support for the students.